Breast Cancer in Indigenous Women Living in Canada: A Scoping Review Protocol - Cole, Katherine (Open Science Framework, 2021)
We aim to collect and categorize the available data pertaining to the biology, risk factors, screening, diagnosis, treatment, surveillance, and survival of breast cancer in Indigenous women living in Canada.